What mental process favours quality decision-making in young soccer players? - Petiot,Grégory Hallé (2017)
Abstract Aim The aim of this research is to identify the mechanisms that lead soccer players to make quality tactical decisions, and how these mechanisms evolve over time. Methods Ninety male youth players training in a professional club in Brazil were submitted to a soccer video test which consists in making tactical decisions when the image freezes. These participants were divided in five groups with 18 players in each of following age levels: Under-11, Under-13, Under-15, Under-17 and Under-20. The dominant statements of verbal reports were distributed in categories that reflect key mechanisms. The frequency of correct tactical answers was calculated for each statement types and Standard Residuals (e) were calculated to verify the influence of the mechanisms on the quality of tactical decision for each age level. Results Results revealed that evaluation statement was related to accurate tactical decisions from Under-15 age level. Conclusion In conclusion, evaluation of perceived information makes better decision makers.